Genomic diversity of major tree species in the Eurasian relict forests of northern Iran - Vatanparast, Mohammad; Madsen, Palle; Sagheb-Talebi, Khosro; Larsen, Jørgen Bo; Ayan, Sezgin; Hansen, Ole K. (Springer Science and Business Media LLC, 2024)
AbstractWe investigated population genetics of the native tree species Acer velutinum Boiss., Fagus orientalis Lipsky, and Quercus castaneifolia C.A. Mey. in the Hyrcanian forests of northern Iran and also F. orientalis populations in the Euro-Siberian and Colchic subregions of northern Türkiye. We used the double-digest RADseq method and genotyped 90 populations and 1,589 individuals across the distribution range of the species. Genome-wide SNPs from 28 populations of A. velutinum, 32 populations of F. orientalis, and 30 Q. castaneifolia revealed higher genetic differentiation among A. velutinum populations than among F. orientalis and Q. castaneifolia. The global FST value was lowest for F. orientalis populations and highest for A. velutinum populations, while the global FIS value was negative for A. velutinum. Demographic history analysis revealed a bottleneck during the last glacial period (11,500—115,000 Kya) for the A. velutinum populations with reduced effective population size (Ne). All three species show multiple bottlenecks and reduced Ne during the Quaternary. Pronounced genetic divergence among A. velutinum populations in the Hyrcanian forests compared to the other two species suggests cryptic speciation. Conversely, F. orientalis and Q. castaneifolia populations showed low levels of genetic structure, suggesting that species-specific factors, such as pollen production and pollination efficiency, may have influenced the genetic patterns within these species in similar environments. The nucleotide diversity of F. orientalis populations in Iran is negatively correlated with altitude (p = 0.046). In contrast, A. velutinum populations show a significant correlation between nucleotide diversity and longitude (p = 0.008). Furthermore, the F. orientalis populations from Türkiye showed a distinct west–east genetic structure and were highly diverged from the Iranian F. orientalis populations.
Keywords: Future forests; Hyrcanian forests; Cryptic speciation; Adaptation potential; Refugia; Quaternary climatic oscillations